2022
DOI: 10.1097/mao.0000000000003521
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 2D BLADE Turbo Gradient- and Spin-Echo Diffusion Weighted Imaging for the Diagnosis of Primary Middle Ear Cholesteatoma

Abstract: ObjectiveTo evaluate the diagnostic accuracy of 2D BLADE turbo gradient- and spin-echo diffusion weighted imaging (TGSE BLADE DWI) for primary middle ear cholesteatoma diagnosis, using qualitative and quantitative methods.Study DesignRetrospective case series.SettingUniversity hospital.PatientsParticipants included those with suspected primary middle ear cholesteatoma after assessment by clinical otorhinolaryngologists combined with magnetic resonance imaging (MRI) examination. Finally, of the 85 ears from 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Due to the lack of unique frequency or phase encoding direction, noise from moving anatomy does not propagate as an artifact along a single direction and oversampling in the center of K space in all directions. The technique has been employed in the pediatric population, as well as for imaging of the head and abdomen, and has exhibited improved image quality in patients with voluntary or involuntary movement [ 17 , 18 , 19 ]. The BLADE technique in our institute was employed in abdominopelvic imaging to address the issue of artifacts caused by pulsation and susceptibility, which present a considerable obstacle when imaging pelvic bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of unique frequency or phase encoding direction, noise from moving anatomy does not propagate as an artifact along a single direction and oversampling in the center of K space in all directions. The technique has been employed in the pediatric population, as well as for imaging of the head and abdomen, and has exhibited improved image quality in patients with voluntary or involuntary movement [ 17 , 18 , 19 ]. The BLADE technique in our institute was employed in abdominopelvic imaging to address the issue of artifacts caused by pulsation and susceptibility, which present a considerable obstacle when imaging pelvic bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the 3D model outperformed junior clinicians and demonstrated equivalent or superior performance to senior experts in identifying cholesteatoma based on CT. Notably, the 3D model achieved outcomes that were on par with or better than those based on human interpretation of MRI, which, despite its higher sensitivity, is a more expensive diagnostic method [22,43,45,[51][52][53].…”
Section: Discussionmentioning
confidence: 99%